Dose response and Bragg curve reconstruction by radiophotoluminescence of color centers in lithium fluoride crystals irradiated with 35 MeV proton beams from 0.5 to 50 Gy. (April 2020) - Piccinini, M.; Nichelatti, E.; Ampollini, A.; Bazzano, G.; De Angelis, C.; Della Monaca, S.; Nenzi, P.; Picardi, L.; Ronsivalle, C.; Surrenti, V.; Trinca, E.; Vadrucci, M.; et al.
Abstract: Passive solid-state radiation detectors, based on the radiophotoluminescence of stable color centers in nominally pure lithium fluoride (LiF) crystals, have been used for advanced diagnostics of the segment up to 35 MeV of the TOP-IMPLART proton linear accelerator for protontherapy applications, under development at ENEA Frascati. In LiF, proton beams generate a spatial distribution of F2 and F3 + aggregate color centers, which efficiently emit radiophotoluminescence in the red-green spectral range under optical pumping around 450 nm. LiF crystals were irradiated with 35 MeV nominal energy protons at several doses of interest for protontherapy (from 0.5 to 50 Gy). For the first time is shown here the possibility of measuring the radiophotoluminescence spectra of proton irradiated LiF even at such low doses and how the signal showed a linear behavior with dose with a good signal-to-noise ratio. A Bragg-curve image, stored as color-center distribution in a LiF crystal after a 50 Gy-dose irradiation in a particular geometry, was acquired in a conventional fluorescence microscope. After appropriate image processing, the signal intensity resulted to be proportional to the linear energy transfer along the whole Bragg curve. By best-fitting it with an ad-hoc analytical formula, the depth-dose distribution was reconstructed and the proton beam energy and energy spread were estimated. Highlights: RPL spectra of 35 MeV proton-irradiated LiF crystals measured from 0.5 to 50 Gy. RPL response linear vs dose with good signal-to-noise ratio under laser excitation. RPL Bragg curve image obtained by a fluorescence microscope at low doses. RPL response along the whole Bragg curve reproduces well the LET curve in LiF.